Social innovation in urban spaces. Issue 3 (2nd September 2018) - Ardill, Nicholas; Lemes de Oliveira, Fabiano
ABSTRACT: Recent international policy advocating for social innovation to be part of strategies to promote sustainable urban development has energised this emerging body of literature. However, there is a need for more sector-specific research to integrate findings on the spatiality of social innovation, co-operative processes, and place-scale relations. This article presents a review (2002–2018) of social innovation in urban spaces. Based on data from 114 publications, the review indicates that research in the spatiality of social innovation can be grouped into three major themes: (1) Spatial planning and community development; (2) Governance; (3) Co-production and service design. The findings suggest that in general the collaboration of end users in place-based development is central to this process of urban change and that process is as significant as the outcome. This article concludes with a research agenda to address identified lacunas.